Etika Guru dalam Pandangan KH. Hasyim Asy'ari: Studi atas Adab al-‘Alim wa al-Muta‘allim di Era Disrupsi - Taulabi, Imam; Adnan, Luthfi; Ubaidila, Syafik (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2024)
The era of disruption has significantly transformed the education system, affecting its systemic, administrative, and technical aspects. These changes have altered the role of educators, challenging their centrality in the learning process as digital platforms increasingly shape educational interactions. In response to these challenges, it is essential to revisit foundational perspectives on teacher ethics to maintain the integrity of education. This study aims to analyze the ethical principles of educators as articulated by KH. Hasyim Asy'ari in Adab al-‘Alim wa al-Muta‘allim and examine their relevance in addressing the challenges of the disruptive era. The research employs a qualitative approach with a content analysis method, focusing on KH. Hasyim Asy'ari's ethical framework and its applicability in contemporary education. The findings indicate that KH. Hasyim Asy'ari emphasizes a balance between spiritual and intellectual competencies as fundamental qualities of educators. His ethical principles advocate for the continuous moral, intellectual, and professional development of teachers to ensure the sustainability of education amid rapid technological advancements. This study contributes to the field of Islamic education by providing a contextualized understanding of classical teacher ethics in the modern era. It highlights the enduring relevance of KH. Hasyim Asy'ari’s ethical framework as a foundation for shaping educators who can navigate and adapt to the evolving educational landscape while maintaining pedagogical integrity.